The brava gente caught on tape: listening in to captured Italian soldiers, sailors and airmen in Britain, 1940-43 - Henry, Alexander (2019)
There is a popular notion that if the Italian armed forces of the Second World War excelled at anything it was in their capacity to surrender en masse. Despite the vast numbers taken prisoner, detailed studies of the experiences of these POWs remain relatively uncommon and the value of this group to furthering our understanding of the Italian experience of war under Fascism is also rarely acknowledged. The existence in the National Archives of hundreds of pages of transcripts of covert British surveillance of Italian POWs has made it possible to engage with their experiences and opinions in much greater depth. The euphemistically termed ‘Special Reports’ present historians with a unique insight into how all levels of Italian soldiery viewed Fascist Italy’s experience of war, 1940-1943. This thesis examines reactions to Italian political leadership, the progress of the war, as well as Italian soldiers’ ‘everyday’ views on sex, war, the enemy, death, food, their allies, bravery, race, and killing. These fascinating documents reveal the complexity of the outlook of these men, which persistent – and influential – national stereotypes and historiographical trends fail to acknowledge.